Structural change, urban congestion, and the end of growth - Volker Grossmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper develops a two-sector R&D-based growth model with congestion effects from increasing urban population density. We show that endogenous technological progress causes structural change if there are positive productivity spillovers from the modern to the traditional sector and Engel's law holds. In turn, urban congestion effects cause a productivity slowdown in the modern sector. Eventually, economic growth may cease in the long-run. We also show that land dilution from a higher workforce may give rise to negative scale effects on GDP per capita. Finally, we investigate how the optimal land allocation depends on the strength of urban congestion effects.
Keywords: O10; O30; O40; 330; congestion; endogenous growth; Engel's law; structural change; urbanization